Intra-Abdominal Testicular Seminoma In A Phenotypic Female: A Case of XY, Disorder of Sex Development Complicated with Seminoma - Abedin, Nafisa; Bushrah, Kazi Nabila; Muktadir, Muhit Reza Md; Hossain, Sajjad; Dey, Bishnu Pada (Sir Salimullah Medical College Journal, 2023)
Disorder of sex development (DSD) complicated with seminoma is infrequently encountered in clinical practice. In order to diagnose the condition histopathological, immunohistochemical, and karyotype analysis can play the pivotal role. Additionally, prognosis of such patients largely depends upon the pathological staging at the time of initial diagnosis. Hence, the aim of this study was to determine the significance of macroscopic and microscopic examination together with immunohistochemical analysis in diagnosis and prognosis of XY, Disorder of sex development (DSD) which is often known to be complicated by intra-abdominal seminoma. A twenty eight year old patient was admitted into Bangabandhu Sheikh Mujib Medical University (BSMMU) presenting with a right sided adnexal mass for one year. Magnetic Resonance Imaging (MRI) showed a large lobulated soft tissue mass in right adnexal region accompanied by infantile uterus. Interestingly, chromosomal analysis of this patient was found to be 46 XY. Post-resection histological studies revealed an intra-abdominal seminoma at a stage of pT2NxMx. The tumour cells expressed immunoreactivity to both Placental Alkaline Phosphatase (PLAP) and C-kit. Sir Salimullah Med Coll J 2023; 31: 60-64